2005
DOI: 10.1111/j.1525-1497.2005.0176.x
|View full text |Cite
|
Sign up to set email alerts
|

A Case of Polymicrobial Endocarditis due to Anaerobic Organisms in an Injection Drug User

Abstract: Endocarditis is a serious complication of injection drug use most commonly due to Staphylococcus aureus. We report a case of tricuspid valve polymicrobial bacterial endocarditis in an injection drug user from 3 oral anaerobes: Actinomyces odontolytica, Veillonella species, and Prevotella melaninogenica. The patient was believed to have acquired these organisms due to his habit of licking the needle in order to gauge the strength of the cocaine prior to injection. The patient was successfully treated with a 6-w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 12 publications
0
14
1
Order By: Relevance
“…Polymicrobial multivalve endocarditis, particularly with biventricular involvement, is uncommon and is mainly described in patients with prolonged intravenous infusion, in intravenous drug-addicted patients, or in patients with congenital heart disease with shunt [3,4]. Our case had none of these predisposing conditions.…”
Section: Discussioncontrasting
confidence: 44%
“…Polymicrobial multivalve endocarditis, particularly with biventricular involvement, is uncommon and is mainly described in patients with prolonged intravenous infusion, in intravenous drug-addicted patients, or in patients with congenital heart disease with shunt [3,4]. Our case had none of these predisposing conditions.…”
Section: Discussioncontrasting
confidence: 44%
“…13 Similar trends hold true for other anaerobic species detected in our study but which rarely cause IE. 13,[19][20][21] Therefore, the reduction in frequency of these bacterial species by amoxicillin may not be clinically significant in the prevention of IE.…”
Section: Discussionmentioning
confidence: 96%
“…An extensive review of the literature since 1939 revealed 24 well-described cases of endocarditis due to Actinomyces including six cases of Actinomyces species [59], two of Actinomyces bovis [10, 11], four of Actinomyces viscosus [1215], two cases of Actinomyces meyeri [16, 17], three of Actinomyces israelii [1820], two of Actinomyces neuii [21, 22], and one of each of Actinomyces septicus [23], Actinomyces muris [24], Actinomyces pyogenes [25], Actinomyces funkei [26], and Actinomyces odontolyticus [27] (Table 1). Almost half of these patients were noted to have predisposing cardiac pathology.…”
Section: Discussionmentioning
confidence: 99%